Correlation of glucose level among venous, gingival and finger-prick blood samples in diabetic patients - Priyanka Chopra; T. S. S. Kumar (Wolters Kluwer Medknow Publications, 2011)
It is essential for a dental surgeon or a periodontist to detect blood glucose level for patients whose signs and symptoms are suggestive of diabetes. Seventy patients in the age group of 40 to 80 years of either sex were selected for the study. The study population included patients with type 1 or type 2 diabetes mellitus. Venous blood was used as a control group, whereas gingival blood and finger-prick blood constituted the study groups I and II, respectively. The percentage deviations of gingival blood glucose level measurements and finger-prick blood glucose level measurements from the standard venous blood glucose level measurements were recorded, which showed that 72.86% of gingival and 68.57% of finger-prick blood glucose level measurements were found to be within ΁15% of the standard venous blood glucose level measurements. All values exhibited significant correlations among each other, but correlations between glucose values obtained using venous and gingival blood samples were higher than the correlations between glucose values obtained using venous and finger-prick blood samples.